Proceedings of the Twenty-First Annual Symposium on Computational Geometry 2005
DOI: 10.1145/1064092.1064140
|View full text |Cite
|
Sign up to set email alerts
|

Efficient computation of query point visibility in polygons with holes

Abstract: In this paper, we consider the problem of computing the visibility of a query point inside polygons with holes. The goal is to perform this computation efficiently per query with more cost in the preprocessing phase. Our algorithm is based on solutions in [13] and [2] proposed for simple polygons. In our solution, the preprocessing is done in time O(n 3 log(n)) to construct a data structure of size O(n 3 ). It is then possible to report the visibility polygon of any query point q in time O((1 + h ) log n + |V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…2). It is easy to arrange a scene such that the number of combinatorially different visibility polygons is Θ(n 4 ) (e.g., see [17]). Therefore it seems likely that the above result is the best we can reach for optimal query time.…”
Section: Visibility Polygon Computationmentioning
confidence: 99%
See 2 more Smart Citations
“…2). It is easy to arrange a scene such that the number of combinatorially different visibility polygons is Θ(n 4 ) (e.g., see [17]). Therefore it seems likely that the above result is the best we can reach for optimal query time.…”
Section: Visibility Polygon Computationmentioning
confidence: 99%
“…Pocchiola and Vegter [13] then showed that if the boundary polygon of the scene and its holes are convex polygons, using visibility complex, V P (q) can be reported in time O(|V P (q)| log n) after preprocessing the scene in time O(n log n + E) time and O(E) space, where E is the number of edges in the visibility graph of the scene. Very recently Zarei and Ghodsi [17] proposed an algorithm that reports V P (q) in O((1 + min(h, |V P (q)|)) log n + |V P (q)|) query time. The preprocessing takes O(n 3 log n) time and O(n 3 ) space.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that the properties of the cells defined in [21] are preserved here. Similar terminologies (not by exactly the same names) and results can also be found in [2,11].…”
Section: Visibility Cell Decompositionmentioning
confidence: 89%
“…Our decomposition is a "finer" version than that given in [21], i.e., each cell defined here is completely contained in a single cell defined in [21]. This implies that the properties of the cells defined in [21] are preserved here.…”
Section: Visibility Cell Decompositionmentioning
confidence: 99%